Kualitas Pelayanan Izin Mendirikan Bangunan (Studi Kasus: Pada Badan Pelayanan Perizinan Terpadu dan Penanaman Modal Kota Palangka Raya) - Muhammad Luthfi Ikhwan (AS-SIYASAH: Jurnal Ilmu Sosial Dan Ilmu Politik, 2020)
This study aims to look at the quality of service granting Building Permit (IMB) at the Integrated Licensing and Investment Services Agency of Palangka Raya City. The thinking framework used is the quality of public services and public bureaucracy. This research uses a qualitative approach, and focuses on qualitative descriptive, data collection is obtained through interviews, observation, and documentation. The results found that in terms of timeliness and ease of service are still not optimal, while in terms of service accuracy and service costs are quite good. The obstacle faced is the factor of waiting for a recommendation from the City Planning, Building and Planting Office of Palangka Raya City in issuing a Building Permit (IMB).